Virtual reality and artificial intelligence : risks and opportunities for your business - Zaralli, Matteo (Routledge/Taylor & Francis Group, 2024)
"Technology is rapidly transforming the way people learn and train, and the integration of virtual reality (VR) and artificial intelligence (AI) could be the next big breakthrough. With the advent of Web 3.0 and the Metaverse, there are endless possibilities for creating immersive and engaging learning environments. However, there is also a need to address the risks and challenges that these technologies present. This book aims to explore the risks and opportunities of VR and AI for coaching and training, with an eye toward the emerging trends of Web 3.0 and the Metaverse. Coaching and training have become increasingly important for companies seeking to develop and retain talent. With the advent of VR and AI technology, there is an opportunity to create immersive and engaging learning environments that could greatly enhance the learning experience. However, there are also risks associated with the use of these technologies, such as data privacy and cybersecurity. This book provides an in-depth analysis of the risks and opportunities of VR and AI for coaching and training, with the goal of helping startup and small business executives understand how to use these technologies responsibly and effectively. Web 3.0 and the Metaverse are radically changing the way people connect and interact online. This has opened the door to a new way of learning and training, which could have significant implications for businesses and their employees. This book explores the emerging trends of Web 3.0 and the Metaverse and how they could change coaching and training. It also provides information on VR and AI technologies that could be used to enhance the learning experience. With an in-depth analysis of the risks and opportunities, this book offers start-up and small business leaders an opportunity to understand how these technologies are changing coaching and training, and how they can use these technologies to improve their business strategies"-- Provided by publisher